Kekayaan Intelektual Sebagai Objek Jaminan Kredit Perbankan: Prospek dan Kendala - Teguh Rizkiawan (Lex Renaissance, 2022)
This study aims to analyze the position of intellectual property rights as and object of bank credit guarantee and the prospects and challenges of intellectual property rights as an object of bank credit guarantee. This is a normative juridical research that uses statutory and conceptual approaches to analyze the formulation of the problem. The results of this study concluded that intellectual property rights are intangible movable objects that can be categorized as collateral for bank credit through fiduciary guarantees. Intellectual property rights as objects of banking credit guarantees have prospects and several obstacles. As the prospects in the future, intellectual property rights will provide the economic growth of Indonesia through the creative economy industry with the promulgation of PP Number 24 of 2022. However, there are obstacles including the absence of a revision of PBI Number 14/15/PBI/2012 which from the banking side, consists of applying the valuation of rights assets intellectual property rights and the need for the establishment of an appraisal institution for intellectual property rights in Indonesia.Keywords: Intellectual Property Rights, Credit Collateral, Banking. AbstrakPenelitian ini bertujuan untuk menganalisis kedudukan hak kekayaan intelektual sebagai benda jaminan kredit perbankan dan prospek serta kendala hak kekayaan intelektual sebagai objek jaminan kredit perbankan. Penelitian ini merupakan penelitian yuridis normatif yang menggunakan pendekatan perundang-undangan dan pendekatan konseptual untuk menganalisis rumusan masalah yang diteliti. Hasil penelitian ini menyimpulkan bahwa hak kekayaan intelektual merupakan benda bergerak yang tidak berwujud dapat dikategorikan sebagai benda jaminan kredit perbankan melalui jaminan fidusia. Hak kekayaan intelektual sebagai objek jaminan kredit perbankan memiliki prospek dan beberapa kendala. Prospek kedepan, hak kekayaan intelektual akan memberikan pertumbuhan perekonomian Indonesia melalui industri ekonomi kreatif dengan diundangkannya PP Nomor 24 Tahun 2022. Namun demikian, terdapat kendala diantaranya belum adanya revisi PBI Nomor 14/15/PBI/2012 dari pihak perbankan dalam menerapkan penilaian terhadap aset hak kekayaan intelektual dan diperlukannya pembentukan lembaga penilai aset hak kekayaan intelektual di Indonesia.Kata-kata Kunci: Hak Kekayaan Intelektual, Benda Jaminan Kredit, Perbankan.